1986
DOI: 10.1152/jn.1986.55.6.1153
|View full text |Cite
|
Sign up to set email alerts
|

Structure-function relationships in rat medullary and cervical dorsal horns. I. Trigeminal primary afferents

Abstract: Intracellular recording and horseradish peroxidase (HRP) labeling were used to examine structure-function relationships in the medullary dorsal horn (MDH) and rostral cervical dorsal horn. In Nembutal-anesthetized rats, 78 trigeminal (V) primary afferent fibers were physiologically characterized and injected with HRP. Axons were sufficiently well stained to reconstruct all of their collaterals in the MDH. Many also extended into the cervical dorsal horn. Except for four axons, which responded best to noxious s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
60
2

Year Published

1993
1993
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(72 citation statements)
references
References 0 publications
10
60
2
Order By: Relevance
“…These observations show the correspondence between the periphery and Sp5I and Sp5O, as suggested by prior anatomical and electrophysiological studies (Nord, 1967(Nord, , 1968Belford and Killackey, 1980;Hayashi, 1980;Arvidsson, 1982;Bates and Killackey;Jacquin et al, 1986Jacquin et al, , 1988Dallel et al, 1990;Jacquin and Rhoades, 1990). In neonatal subjects, the foci of 2DG uptake corresponded well to that of the adult rat (Gonzalez and Sharp, 1985).…”
Section: Brainstem Trigeminal Complexsupporting
confidence: 85%
See 1 more Smart Citation
“…These observations show the correspondence between the periphery and Sp5I and Sp5O, as suggested by prior anatomical and electrophysiological studies (Nord, 1967(Nord, , 1968Belford and Killackey, 1980;Hayashi, 1980;Arvidsson, 1982;Bates and Killackey;Jacquin et al, 1986Jacquin et al, , 1988Dallel et al, 1990;Jacquin and Rhoades, 1990). In neonatal subjects, the foci of 2DG uptake corresponded well to that of the adult rat (Gonzalez and Sharp, 1985).…”
Section: Brainstem Trigeminal Complexsupporting
confidence: 85%
“…In some instances, there was a slight expansion of 2DG uptake into regions outside the vibrissa representation zone, i.e., the substantia gelatinosa and the lamina V. This could be mediated by laminae III/IV caudalis neurons, some of which have dendritic trees extending into the superficial laminae (Gobel, 1979;Sharp et al, 1988). The uptake extending into the deeper lamina V may also be due to the presence of some low-threshold mechanoreceptive neurons at the border of the laminae IV and V, which could be activated by whisker stimulation (Hu et al, 1981;Jacquin al et al, 1986).…”
Section: Brainstem Trigeminal Complexmentioning
confidence: 99%
“…It has been reported that trigeminal nociceptive information is sent to the nucleus caudalis of the trigeminal spinal nucleus and upper cervical cord (1)(2)(3). Following peripheral inflammation, Fos studies have revealed that two peaks of Fos protein-like immunoreactive cells (Fos protein-LI cells) are expressed; one in the transition zone between the trigeminal spinal nucleus interpolaris and caudalis (Vi/Vc zone), and one in the caudal laminated region between the caudalis and upper cervical dorsal horn (Vc/C 1,2 zone) (4).…”
Section: Introductionmentioning
confidence: 99%
“…These findings have provided a general picture of the termination pattern of vibrissa afferents but have not clarified the characteristics of the central terminations from functionally different afferent fibers. Studies using the intra-axonal staining technique have revealed that the morphologies of central terminations from low-threshold mechanoreceptive vibrissa afferents differ between FA and SA types within each trigeminal nucleus (Shigenaga et al, 1990;Miyoshi et al, 1994) and between different nuclei (Jacquin et al, 1986a(Jacquin et al, ,b, 1988(Jacquin et al, , 1989Shigenaga et al, 1990;Miyoshi et al, 1994). These results suggest that the characteristics of the morphology of primary afferent terminations are well correlated, with a morphologic segregation within the cytoarchitectonically different zones of the trigeminal sensory nuclei, and that sensory information from functionally distinct fibers is processed in a characteristic manner in the individual nuclei.…”
mentioning
confidence: 99%